The Mediation Effects of COVID Vaccine Anxiety, Safety, and Fear on the Relationships between COVID-19 Threat and Efficacy Levels with Parents’ Intent to Vaccinate Children (Journal of International Crisis and Risk Communication Research, 2023)
Given the updated, ongoing recommendations for the COVID vaccine series and booster for children ages 6 months and older yet vaccine coverage remaining at less than 50% among children, it is critical for public health communicators to understand sources of vaccine hesitance among parents. A national survey of parents identifies the mediating effects of vaccine anxiety, safety, and fear on the relationships between COVID-19 threat and efficacy with behavioral intentions to vaccinate. Anxiety mediated the relationships between both threat and efficacy with parents’ behavioral intentions to vaccinate their children. Vaccine anxiety, safety, and fear mediated parents’ decisions to vaccinate themselves. Theoretical and applied implications are reviewed.